2017
DOI: 10.1016/j.foodqual.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of reducing fat, salt and sugar in commercial foods on consumer acceptability and willingness to pay in real tasting conditions: A home experiment

Abstract: International audienceDecreasing obesity or cardiovascular disease can be achieved by eating healthier foods with reduced contents of fat, salt and sugar. However, these ingredients have a significant impact on the sensory quality of the food products that contain these ingredients, especially cooked sausage, chorizo, dry sausage, cheese and muffins. In this study, consumer appreciation of these five commercialized products (non reformulated versions) and their respective reformulated versions with reduced con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
23
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 35 publications
11
23
0
2
Order By: Relevance
“…For instance, sensory education measures tailored to individual liking could provoke a shift in liking toward more complex foods in persons who strongly favor fatty foods, thereby leading to reduced acceptance of fattysalted or fatty-sweetened foods and greater dietary variety [52]. Indeed, previous works demonstrated that the preferred amounts of fat, salt and sugar in foods have an innate basis that can be changed by modifying the frequency of sensory exposure to the fatty, salty and sweet tastes [53][54][55]. An effort can also be done at the environmental level, via improvement in the food product supply available, such as products with reduced content of saturated and trans fats, sodium or sweet, that are tasty and offer satisfaction to the consumer.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, sensory education measures tailored to individual liking could provoke a shift in liking toward more complex foods in persons who strongly favor fatty foods, thereby leading to reduced acceptance of fattysalted or fatty-sweetened foods and greater dietary variety [52]. Indeed, previous works demonstrated that the preferred amounts of fat, salt and sugar in foods have an innate basis that can be changed by modifying the frequency of sensory exposure to the fatty, salty and sweet tastes [53][54][55]. An effort can also be done at the environmental level, via improvement in the food product supply available, such as products with reduced content of saturated and trans fats, sodium or sweet, that are tasty and offer satisfaction to the consumer.…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to a lower level of salt, consumers do not prefer too low a level of this ingredient, although the health effect of food is appreciated by them (Rødbotten et al, ; Żakowska‐Biemans, Sajdakowska, & Issanchou, ). However, reformulations, for example, reducing fat, salt, and sugar content, may enable improvements in the product competitiveness on the food market (Romagny, Ginon, & Salles, ).…”
Section: Discussionmentioning
confidence: 99%
“…This is probably due to the socio-demographic characteristics of this group of consumers. (Romagny, Ginon, & Salles, 2017).…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…Solid fats are commonly used in processed foods to confer technological and sensory properties desired by the consumer [1]. However, trans, saturated, and recently interesterified fats have been associated with negative health related effects, such as increasing the risk of obesity, diabetes, cancer, and cardiovascular diseases [2,3].…”
Section: Introductionmentioning
confidence: 99%